The Recent Variation of Ice Sheet in Mizuho Plateau - Mae, Shinji (1979)
P(論文) On the basis of the glaciological survey carried out by the Japanese Antarctic Research Expedition in Mizuho Plateau, thinning of ice sheet in the observed area is discussed. The vertical profiles of oxygen isotope (O^<18>) and ice temperature at Mizuho Station are also explained by the thinning of ice sheet which commenced 100 years ago. A simple calculation of basal shear stress shows the unstable state of the ice sheet in Mizuho Plateau. departmental bulletin paper